2016
DOI: 10.1007/s10934-016-0214-z
|View full text |Cite
|
Sign up to set email alerts
|

A facile strategy to fabricate carboxyl-rich carbon spheres with copper-based MOFs through coordination bond

Abstract: A new composite (CCSs/MOFs) of carboxylrich carbon spheres (CCSs) and copper-based metal-organic frameworks (MOFs) was for the first time prepared. The CCSs/MOFs composite was synthesized by the coordinated growth of high surface area and porous MOFs, [Cu 3 (BTC) 2 (H 2 O)] n (HKUST-1), on the surface of the functionalized CCSs obtained through a one-step hydrothermal carbonization of glucose with acrylic acid at 180°C for 24 h. The resulting composites showed a core/ shell structure with a tunable diameter ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, the open skeleton structure of MOFs without strong non-specific adsorption and with poor dispersion. For this reason, some scholars try to combine it with carbon nanomaterials, Kumar found that hybrid nanocomposites of GO with ZIF-8 exhibited tunable nanoscale morphology and porosity, and this composite has a high storage rate of CO 2 [26]; Jabbari developed a hybrid nanocomposites based on Cu-BTC MOF, GO, CNT, and Fe 3 O 4 magnetic nanoparticles via a simple green solvothermal method, at which GO and CNT were used as platforms to load nanostructured Cu-BTC MOF and Fe 3 O 4 MNPs and the hybrid nanomaterials showed enhanced pollutant adsorption capacity compared to that of the parent materials [27]; Ge Chunhua prepared carboxyl-rich carbon spheres (CCSs) and copper-based metal–organic frameworks (MOFs), and it is disclosed that carboxyl-rich groups of the CCSs could substantially enhance the connection with the Cu ion in MOF, and benefit for the homogenous surface growth of HKUST-1 on the core of CCSs [28]. Many studies have shown that the rich functional groups on the surface of GO make it a potential platform to promote the growth of MOF and enhance its dispersing power.…”
Section: Introductionmentioning
confidence: 99%
“…However, the open skeleton structure of MOFs without strong non-specific adsorption and with poor dispersion. For this reason, some scholars try to combine it with carbon nanomaterials, Kumar found that hybrid nanocomposites of GO with ZIF-8 exhibited tunable nanoscale morphology and porosity, and this composite has a high storage rate of CO 2 [26]; Jabbari developed a hybrid nanocomposites based on Cu-BTC MOF, GO, CNT, and Fe 3 O 4 magnetic nanoparticles via a simple green solvothermal method, at which GO and CNT were used as platforms to load nanostructured Cu-BTC MOF and Fe 3 O 4 MNPs and the hybrid nanomaterials showed enhanced pollutant adsorption capacity compared to that of the parent materials [27]; Ge Chunhua prepared carboxyl-rich carbon spheres (CCSs) and copper-based metal–organic frameworks (MOFs), and it is disclosed that carboxyl-rich groups of the CCSs could substantially enhance the connection with the Cu ion in MOF, and benefit for the homogenous surface growth of HKUST-1 on the core of CCSs [28]. Many studies have shown that the rich functional groups on the surface of GO make it a potential platform to promote the growth of MOF and enhance its dispersing power.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all CP synthesis methods have been employed to prepare nano- and microstructures, such as direct precipitation, hydrothermal reaction, microwave/ultrasound driven synthesis, electrochemistry, and so on [ 16 , 20 , 21 , 22 ]. Hence, a variety of nano-and microstructures have been achieved, including spheres, cubes, rods, wires, sheets, ribbons, straw-sheaf, and so on [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. However, structuring CP at the nano- and micro-scales is a nascent field and it is still a challenge to fabricate complex or desired CP nano- and microstructures through a facile and controllable approach.…”
Section: Introductionmentioning
confidence: 99%